GENOME-WIDE SNP ALLELOTYPING OF HUMAN COHORTS BY POOLED DNA SAMPLES - V. N. Babenko; V. N. Maximov; E. V. Kulakova; E. S. Safronova; M. I. Voevoda; E. I. Rogaev (Вавиловский журнал генетики и селекции, 2015)
The research concerns the task of identification of contrasted single nucleotide polymorphisms (SNPs) obtained in genome-wide pooled allelotyping of 16 human cohorts, comprising healthy and ill persons, by the nested case–control approach. The genotyping platform was the Illumina Omni1S chip with 1.2 million markers. The mean pooled sample size was about 200 individuals. The candidate selection was based on statistical comparison of allele frequencies in a “case–control” study. Samples of ill patients show significant deviations from healthy persons in the numbers of significantly differing polymorphisms. The variance of allele frequencies among repeats in a single cohort was less than that in random choice of pairs from different cohorts.